2021
DOI: 10.1093/eurpub/ckab165.056
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy among Tunisian cancer patients in the Salah Azaeiz Institute of Cancer

Abstract: Background Vaccination against SARS-CoV-2 is the most effective way to stop the pandemic and to avoid its related deaths. COVID-19 vaccine hesitancy, represent now a major hurdle to achieve herd immunity. Cancer patients constitute a prioritized group for COVID-19 vaccination as they are particularly vulnerable to severe infection and death. The aim of this study was to assess vaccine hesitancy among cancer patients of the Salah Azaiez Institute (SAI) of cancer and to identify its knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Like recent international studies, we found that most cancer patients intended to be or were vaccinated. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Our research also found that additional cancer stakeholder groups, such as family members, HPs, and NGOs, all expressed pro COVID-19 vaccination attitudes and behaviors.…”
Section: Accessibilitymentioning
confidence: 67%
See 4 more Smart Citations
“…Like recent international studies, we found that most cancer patients intended to be or were vaccinated. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Our research also found that additional cancer stakeholder groups, such as family members, HPs, and NGOs, all expressed pro COVID-19 vaccination attitudes and behaviors.…”
Section: Accessibilitymentioning
confidence: 67%
“…All stakeholder groups reported barriers to COVID‐19 vaccination uptake in this population, supporting the previous research. Barriers included lack of confidence in science and vaccine efficacy, 16 , 19 , 21 , 23 , 24 fear of side effects, 16 , 21 , 22 , 23 , 24 , 25 , 26 , 30 belief that COVID‐19 is benign, 16 , 23 , 25 and concern about vaccine impact on treatment. 18 , 22 , 26 Notably, most hesitation related to the lack of information about vaccine efficacy and impacts within the cancer context, rather than general antivaccination sentiment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations